2022
DOI: 10.1177/15266028221081078
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Case Series and Literature Review on Durability of Stents in the Thoracic Outlet

Abstract: Purpose: The aim of this paper was to report our experience with arterial and venous endovascular stent placement in the thoracic outlet (TO) and review available literature. Methods: All patients that underwent arterial or venous stent placement in the TO between 2013 and 2020 in 5 Dutch vascular teaching-hospitals were retrospectively identified. Primary endpoint was symptomatic stent failure due to stenosis, chronic or posture dependent compression, fracture, or occlusion of the stent. Secondary endpoints w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A total of five patients with VTOS received primary stent placement ( N = 2) or postoperative stent placement ( N = 3) with mixed results. This was in line with our recently published case series and literature review, where we found that both venous and arterial stents in the thoracic outlet have a considerable risk of failure, especially in patients who were stented without prior TOD ( 4 ). Moreover, due to a limited amount of evidence and reported mixed results, stent placement in the thoracic outlet is discouraged in the most recent ESVS guideline ( 22 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A total of five patients with VTOS received primary stent placement ( N = 2) or postoperative stent placement ( N = 3) with mixed results. This was in line with our recently published case series and literature review, where we found that both venous and arterial stents in the thoracic outlet have a considerable risk of failure, especially in patients who were stented without prior TOD ( 4 ). Moreover, due to a limited amount of evidence and reported mixed results, stent placement in the thoracic outlet is discouraged in the most recent ESVS guideline ( 22 ).…”
Section: Discussionsupporting
confidence: 90%
“…Invasive treatment consists of thoracic outlet decompression surgery (TOD), and in the presence of acute thrombosis it can be preceded by catheter directed thrombolysis (CDT). Additional percutaneous transluminal angioplasty (PTA) and/or venous stenting might be used in selected cases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…All seven recurrent occlusions that occurred during follow-up, transpired in patients who were put on antiplatelet therapy, while none occurred in the patients using vitamin K antagonists or DOACs which might suggest that antiplatelet therapy is an inadequate therapy for postoperative ATOS patients. However, three out of seven re-occlusions occurred in patients with subclavian artery stents known for an increased risk of recurrent TE events and therefore an important confounder (by indication) in this study ( 15 ). Based on our series and currently available evidence an optimal postoperative antithrombotic treatment strategy for prevention of recurrent arterial occlusions in ATOS patients is still lacking.…”
Section: Discussionmentioning
confidence: 81%
“…Stent placement within the subclavian arteries and veins has been shown to have poor durability, likely due to mechanical motion within this region causing repetitive stress and structural failure of the stent. 2 Generally, stent placement in the subclavian vessels is not recommended. 3 This is particularly problematic in dialysis patients who rely on patent outflow veins for their dialysis access and are often not good surgical candidates for definitive decompressive surgery.…”
Section: Discussionmentioning
confidence: 99%